2021
DOI: 10.3390/ph14050409
|View full text |Cite
|
Sign up to set email alerts
|

Drug Delivery Approaches for Managing Overactive Bladder (OAB): A Systematic Review

Abstract: Overactive bladder syndrome (OAB) is characterised by urgency symptoms, with or without urgency incontinence, usually with frequency and nocturia and severely affects the quality of life. This systematic review evaluates the various drug delivery strategies used in practice to manage OAB. Advanced drug delivery strategies alongside traditional strategies were comprehensively analysed and comparatively evaluated. The present review was conducted according to the preferred reporting items for systematic reviews … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 87 publications
0
16
0
Order By: Relevance
“…An assessment of the risk of bias was carried out for each included article by evaluating six domains: rationale of research, description of the methodology, characterization and testing, description of result, description of discussion, and overall conclusion, as shown in Tables S2 and S3 (Supplementary Materials). [32]. The current risk of bias framework was modified from the Cochrane Handbook for Systematic Reviews of Interventions and standard quality assessment criteria for evaluating primary research papers from a variety of fields [33,34] adopting the redundancy and mapping approach [35][36][37].…”
Section: Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…An assessment of the risk of bias was carried out for each included article by evaluating six domains: rationale of research, description of the methodology, characterization and testing, description of result, description of discussion, and overall conclusion, as shown in Tables S2 and S3 (Supplementary Materials). [32]. The current risk of bias framework was modified from the Cochrane Handbook for Systematic Reviews of Interventions and standard quality assessment criteria for evaluating primary research papers from a variety of fields [33,34] adopting the redundancy and mapping approach [35][36][37].…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Many researchers have reported the superiority of eucalyptus oil over other terpenes and fatty acid-containing oils in topical gel formulations. Rajan and Vasudevan [55] and Akhlaq et al [32] found that it was more effective than other penetration enhancers in permeation enhancement from a transferosomal gel of ketoconazole and a hydrogel of pioglitazone. Furthermore, eucalyptus oil increased the permeation and retention in dermal and epidermal layers of hydrocortisone acetate compared to clove oil and lemongrass oil within a microemulgel formulation [56].…”
Section: Eucalyptus Oilmentioning
confidence: 99%
“…Pradeep Tyagi's team also used a PEG‐PLGA‐PEG hydrogel in a rat model to release capsaicin, which is used for the treatment of overactive bladder. It has been shown that the use of the temo‐sensitive hydrogel as a delivery vehicle for the therapeutic substance can lead to a reduction in bladder contractions, but does not completely reduce micturition reflexes 59,60 . The team of Sang Hyun Kim et al analyzed in vitro and in vivo the effect of different concentrations of Poloxamer P407 containing 0.2% w/w fluorescein isothiocyanate dextran as a fluorescent probe on the retention time of the hydrogel in the urinary bladder.…”
Section: Applications Of Hydrogel Materials In the Treatment Of Urina...mentioning
confidence: 99%
“…The diagnosis of OAB is based primarily on patient-reported ailments. Those ailments may considerably deteriorate the quality of life and cause various social, work-related, psychological and sexual problems [2]. Research conducted in Europe and the United States showed that the manifestations of OAB were present in more than 10% of the general population, with the risk double in persons > 65 years of age [3].…”
Section: Introductionmentioning
confidence: 99%